Exploration of Human Resources in Transformational Leadership toward Business Sustainability of Indonesian Small and Medium Enterprises - Istikhoroh, Siti; Lasiyono, Untung; Noerchoidah, Noerchoidah; Ardhiani, Mutiara Rachma; Arindra, Fairuza (International Review of Management and Marketing, 2025)
In Indonesia, Small and Medium Enterprises (SMEs) are business units providing broad socio-economic benefits to the community and absorbing 97% of the national workforce. The large role is not balanced with the ability to continue growing and surviving in the global economic arena. Therefore, this research aimed to analyze several variables influencing Business sustainability (BS) in functional relationships including exploration of human resources (EHR), transformational leadership (TL), and Network Communication (NC). Data were collected by distributing questionnaires to 398 respondents and analyzed using structural equation models - partial least square (SEM-PLS) statistical method based on SmartPLS software. The results of the analysis showed that there was a direct influence between EHR on BS, EHR on TL, and NC on BS. The influence of EHR on BS through TL was not reported. However, NC succeeded in increasing the influence of EHR and TL on BS. This research enriched the principles of strategic management science in the field of formulating measuring instruments for determining BS. At the practical level, alternative solutions were provided to the problem of low BS using knowledge from business, management, finance, and communication sciences.